2019
DOI: 10.4028/www.scientific.net/kem.829.54
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Zirconium Oxide-Doped Hydroxyapatite

Abstract: Various bioceramic materials including zirconia and hydroxyapatite have been developed for various applications. Hydroxyapatite (Ca10(PO4)6(OH)2, HAp) is one of the most interesting features of calcium phosphate-based bioceramic that widely used in various applications especially for bio-application, bone engineering, and dentistry. However, the applications of pristine HAp have limited due to low load bearing applications. The wet chemical precipitation techniques was used to synthesize the solids based on zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Studies reported a less than 2% bio-implant failure after following up for several years, assuring the clinical success of the HA powder (HAp) in biomedical applications [41][42][43][44][45][46][47]. However, sudden failure of HAp-based bio-implants was reported recently, due to deterioration resulting from faster dissolution of the HAp under body fluid conditions as HAp is brittle in nature and has poor crystallinity [47][48][49][50][51][52]. Researchers have been investigating the effects of a HAp mixed-EDM process on modified surface characteristics over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported a less than 2% bio-implant failure after following up for several years, assuring the clinical success of the HA powder (HAp) in biomedical applications [41][42][43][44][45][46][47]. However, sudden failure of HAp-based bio-implants was reported recently, due to deterioration resulting from faster dissolution of the HAp under body fluid conditions as HAp is brittle in nature and has poor crystallinity [47][48][49][50][51][52]. Researchers have been investigating the effects of a HAp mixed-EDM process on modified surface characteristics over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Sterically, the ZrO6 that's larger than the TiO6 would logically stay on the nanofiber surface to minimize the distortion of the nanofiber's TiO6-dominated crystal lattice. Thus-surfaced ZrO6 can potentially help bone-tissue adhesion, as well-established in the literature [27,33,34] . Further, the interlayer K + cations near the ZrO6 in the K-titanate nanofiber could be more easily (hence more rapidly) replaced by Ca 2+ cations in body fluid to promote the rapid formation of hydrated calcium phosphates (or hydroxyapatite) on the nanofiber, like other labs reported in the literature using the simulated body fluid (SBF) [18,35] .…”
Section: Zirconium Dopingmentioning
confidence: 83%
“…The strong bonding between the hydroxyapatite coating and the titanate nanofiber substrate surface can chemically secure the bone tissue's long-term strong adhesion to the nanofibersupported hydroxyapatite, forming an ideal osteogenic/osteoconductive environment [18] . The thusoptimized surface of titanate nanofibers for developing a new bone scaffold can complement other lab methods in promoting the bone scaffold's osteoconductivity [27,33,34,36] . In basic chemistry, this work has demonstrated an innovative and cost-effective method for doping Zr (IV) into the titanate nanofiber lattice, which seems new and important in orthopedic nanomedicine.…”
Section: Zirconium Dopingmentioning
confidence: 99%
“…5 Kelemahan karbonat apatit tersebut dapat diatasi dengan penambahan bahan keramik lainnya yaitu zirkonia yang akan meningkatkan kekuatan mekanik bahan keramik yang pertama. 6 Zirkonia adalah material keramik yang memiliki sifat biokompatibilitas yang baik, sifat mekanik yang baik, tahan terhadap korosi dan resistensi terhadap kerusakan. Sifat mekanik yang tinggi dari zirkonia dapat dimanfaatkan sebagai bahan penguat dari keramik yang pertama.…”
Section: Pendahuluanunclassified
“…Karakteristik sintering tahap awal adalah adanya gambaran ikatan yang terbatas pada antar partikel . 6 Selain itu beberapa daerah sintering dapat teramati dengan baik, hal ini disebabkan oleh ukuran partikel yang lebih kecil. Struktur zirkonia merupakan keramik bioinert yaitu stabil dalam tubuh manusia dan tidak menunjukkan respon yang berbahaya.…”
Section: Pembahasanunclassified